2020
DOI: 10.17267/2238-2704rpf.v10i3.2931
|View full text |Cite
|
Sign up to set email alerts
|

Perfil de trabalhadores com lombalgia atendidos em um serviço de saúde

Abstract: INTRODUÇÃO: As transformações no mundo do trabalho têm propiciado o acúmulo de tarefas, exigências de polivalência e aumento do ritmo de trabalho, ocasionando um aumento de lombalgias. OBJETIVO: Descrever o perfil de trabalhadores com lombalgia, atendidos em uma unidade especializada em Saúde do Trabalhador da Baixada Santista. MÉTODOS: Trata-se de um estudo observacional transversal e exploratório. Ocorreu análise documental de prontuários abertos de trabalhadores atendidos no Centro de Referência em Saúde do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
1
0
1
Order By: Relevance
“…In this study, it was identified that the predominant epidemiological profile was females aged between 33 years and 66 years. In the literature, we found that the incidence of low back pain occurs predominantly in men over 40 years old and in women over 50 years old (VALADARES et al, 2020) The predisposing factors for the development of low back pain are prolonged sitting, intense physical effort, repetitive movements, stress and conflict in the work environment (SIMAS et al, 2020). Studies indicate that these factors are mostly performed by women, as they are the ones who are subject to domestic work, cleaning, food and textiles, in addition to anatomical particularities such as smaller stature, muscle mass and more fragile joints, this justifies the high incidence of low back pain in females, adding to the findings in this study (BOTTAMEDI 2016;SIMAS 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, it was identified that the predominant epidemiological profile was females aged between 33 years and 66 years. In the literature, we found that the incidence of low back pain occurs predominantly in men over 40 years old and in women over 50 years old (VALADARES et al, 2020) The predisposing factors for the development of low back pain are prolonged sitting, intense physical effort, repetitive movements, stress and conflict in the work environment (SIMAS et al, 2020). Studies indicate that these factors are mostly performed by women, as they are the ones who are subject to domestic work, cleaning, food and textiles, in addition to anatomical particularities such as smaller stature, muscle mass and more fragile joints, this justifies the high incidence of low back pain in females, adding to the findings in this study (BOTTAMEDI 2016;SIMAS 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In this context, Ergonomics aims to improve health and awaken the importance of this study, as the workspace must ensure comfort and safety. A company that seeks to offer an ergonomically appropriate environment will consequently increase its productivity (SILVA et al, 2020).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…As for the characteristics of low back pain, it is described as pain manifested between the costal margins and the gluteal fold, followed by painful restriction in the performance of movements. On the other hand, pain in the cervical segment of the spine is called cervicalgia, and is responsible for generating frequent biomechanical stresses that can manifest acute 3 and temporary symptoms, in addition to accelerating the degenerative process of the vertebral structure and joints (SIMAS et al, 2020).…”
Section: Wmsd In Cashiersmentioning
confidence: 99%
“…Quanto as características da lombalgia, é descrita como dor manifestada entre as margens costais e a prega glútea, seguida de restrição dolorosa na realização de movimentos. Por sua vez, a dor no seguimento cervical da coluna é chamada de cervicalgia, sendo responsável por gerar estresses biomecânicos frequentes que podem manifestar sintomas agudos 3 e temporários, além de acelerar o processo degenerativo da estrutura vertebral e das articulações (Silva-Pereira et al, 2017;Simas et al, 2020., Sato et al, 2019.…”
Section: Introductionunclassified